Evaluation of clavulanic acid recovery techniques from Streptomyces clavuligerus cultivation broths - Yeison Agudelo-Arenas, Rigoberto Ríos-Estepa, David Gómez-Ríos (Journal of Applied Pharmaceutical Science, 2024)
Clavulanic acid (CA) is a soft β-lactam antibiotic with a strong inhibitory effect on β-lactamase enzymes and it is produced by the filamentous Gram-positive bacterium Streptomyces clavuligerus (S. clavuligerus) as a secondary metabolite; the complete pathway (known as the clavam pathway) derives from the condensation of arginine and glyceraldehyde-3-phosphate, as anabolic precursors. In this work, the potential of two distinct operations for CA recovery was re-evaluated: first, the adsorption of CA through the utilization of the anion exchange resin Amberlite IRA 400, and second, the application of liquid–liquid extraction systems. For the liquid–liquid extraction, two experimental designs were developed aimed at finding the best conditions of the process. For the case of adsorption, the same experimental design, used in the previous strategy, was carried out, for comparison purposes. CA loss was minimized at 10°C and pH 2.0. The adsorption was favored by increasing the adsorbent-to-liquid ratio. Thus, the highest separation was attained in the range of 40%–45% solid/liquid ratio, adsorbing a mean value of 47.7% of the CA present in the broth. Results showed that there is still room for further improvements in CA recovery using both, adsorption and extraction, as the most advantageous techniques.
Keywords: Streptomyces clavuligerus, clavulanic acid, separation processes, liquid–liquid extraction, adsorption, bioprocess